PERANAN WHATSAPP SEBAGAI MEDIA PENEGUHAN IMAN BAGI UMAT DI LINGKUNGAN BENEDIKTUS PAROKI SANTA MARIA DIANGKAT KE SURGA PALUR - Jantika, Centuri; Ispuroyanto, Yoseph (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2024)
This research was motivated by rapid technological developments that can change patterns of human behavior, especially in terms of praying online. This study aims to determine the role of WhatsApp as a medium of faith confirmation for people in the St. Benedict, Parish of Santa Maria Assumption Palur, Karanganyar. Data collection was carried out by observation, interviews, community meetings, and questionnaires. This research was conducted using a mixed approach between qualitative and quantitative, but leaning more towards qualitative. The collected data was validated by means of triangulation. The results of this study indicate that most people feel that WhatsApp has a role as a medium for strengthening the people's faith. They feel affirmed and think that WhatsApp is able to find God through social media. Meanwhile, there are some people who feel that WhatsApp is less helpful when it comes to praying because it is considered less solemn. The people hope that WhatsApp can be used as a means of strengthening faith through what is shared by the people.